Design of Ergonomic Lesehan Chair to Minimize Musculoskeletal Disorder When Carrying Out Student Learning Activities in Confined Spaces - Nisrina, Nabila Ratu; Andrianto, Andrianto; Ramawisari, Ica (JTI: Jurnal Teknik Industri, 2024)
The increasing population has an impact on limited land, especially boarding houses for students. The room size for residential boarding houses is limited so that supporting facilities such as tables and chairs are readjusted. Lesehan tables are often used as furniture options for most student boarding houses, due to their simple shape and affordable prices. However, this is not supported by the ability of the lesehan table to accommodate the ergonomic needs of the user's sitting, which if it lasts long and repetitive will result in musculoskeletal disorder. Therefore, the design of ergonomic lesehan chairs is needed for student productivity and health. The research method used is a mix method starting with direct observation of boarding houses around Bandung, literacy studies related to ergonomics, anthropometry and sitting on the floor. The design method is UCD where the user's problems are solved by prioritizing their needs. The results obtained with this design can reduce pain in several parts of the body, can support student learning productivity and to minimize musculoskeletal disorder.